Mrs. Pollifax and the lion killer - Gilman, Dorothy, 1923- (New York : Fawcett Columbine, 1996)
Part-time CIA agent Emily Pollifax accompanies her young friend, Kadi Hopkirk, to Africa on a mission to stop terrorists from disrupting the coronation of Sammat, Kadi's childhood friend, as the new king of Ubangiba
A novel
930
Keywords: Pollifax, Emily (Fictitious character) -- Fiction; Intelligence service -- United States -- Fiction; Women spies -- Africa -- Fiction; Spy stories